BERIBERI NEUROPATHY SECONDARY TO SLIMMING DIET: A CASE REPORT - Gülçin Kaymak Karataş; Aliye Kapukıran Tosun; Reha Kuruoğlu (Archives of Rheumatology, 2002)
The most common cause of thiamine deficiency is chronic alcoholism. It may also occur in patients with impaired nutrition from other causes. Dry beriberi that is characterized with peripheral neuropathy is one of the clinical feature of thiamine deficiency. In this case report we present a patient whose peripheral neuropathy was attributed to thiamine deficiency because of a hard slimming diet.